Freshwater input to the Arctic fjord Hornsund (Svalbard) - Błaszczyk, Małgorzata; Ignatiuk, Dariusz; Uszczyk, Aleksander; Cielecka-Nowak, Katarzyna; Grabiec, Mariusz; Jania, Jacek A.; Moskalik, Mateusz; Walczowski, Waldemar (Polar research, 2019)
Glaciers draining to the Hornsund basin (southern Spitsbergen, Svalbard) have experienced a significant retreat and mass volume loss over the last decades, increasing the input of freshwater into the fjord. An increase in freshwater input can influence fjord hydrology, hydrodynamics, sediment flux and biota, especially in a changing climate. Here, we describe the sources of freshwater supply to the fjord based on glaciological and meteorological data from the period 2006 to 2015. The average freshwater input from land to the Hornsund bay is calculated as 2517 ± 82 Mt a−1, with main contributions from glacier meltwater runoff (986 Mt a−1; 39%) and frontal ablation of tidewater glaciers (634 Mt a−1; 25%). Tidewater glaciers in Hornsund lose ca. 40% of their mass by frontal ablation. The terminus retreat component accounts for ca. 30% of the mass loss by frontal ablation, but it can vary between 17% and 44% depending on oceanological, meteorological and geomorphological factors. The contribution of the total precipitation over land excluding winter snowfall (520 Mt a−1), total precipitation over the fjord area (180 Mt a−1) and melting of the snow cover over unglaciated areas (197 Mt a−1) to the total freshwater input appear to be small: 21%, 7% and 8%, respectively.